1996
DOI: 10.1007/bf03207767
|View full text |Cite
|
Sign up to set email alerts
|

Variant high-origin radial artery: a bilateral case

Abstract: During a dissection of both upper extremities, an abnormally high origin of the radial a. was found on each side. However, the arterial patterns were not the same. On the right side, the radial a. arose 2 cm above the junction of the two roots of the median n. On the left side, the radial a. arose from the brachial a. 3 cm distal to the origin of the profunda brachii a. The course of these arteries in the forearm were normal. However, in the hand, on the right side, the contributions of the radial and ulnar aa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…All of these reports describe the course of the aberrant vessel as lateral to the usual radial artery. There are no descriptions in the reconstructive and anatomical literature of a superficial and medial branch originating from the radial artery 1.5 cm Weathersby (1956) High origin of radial artery 408 Upper extremities studied revealed departure from normal textbook anatomy in 18.8% of specimens Coleman and Anson (1961) High origin of radial artery 650 Dissected specimens studied Persistent median artery Kadanoff and Balkansky (1966) Duplication of radial artery Case report Small and Millar (1985) Radial artery passing deep to the pronator teres Case report Poteat (1986) Absent radial artery Cadaver dissection single specimen Uglietta and Kadir (1989) High origin of radial artery 100 Upper extremity arteriograms reviewed revealed anomalies of the radial artery in 9% of cases Hedén and Gylbert (1990) Superficial dorsal antebrachial artery Case report Bass (1991) Hypolasia of radial artery Case report e association with VATER syndrome Otsuka and Terauchi (1991) Aberrant dorsal course of radial artery around Lister's tubercle Case report Madaree and McGibbon (1993) Absence of perforators from the radial artery to skin Case report Funk et al (1995) Distal origin of radial artery deep to pronator teres Review of experience with 52 forearm flaps Superficial dorsal antebrachial artery High origin of radial artery Lee et al (1995) Hypoplasia of radial artery Case report e association with KlippeleFeil syndrome Mordick (1995) Aberrant midaxial vessel arising directly from axillary artery Case report Icten et al (1996) High origin of radial artery Case report Sasaki et al (2000) Superficial dorsal antebrachial artery Case report Porter and Mellow (2001) Absent radial artery Case report Rodríguez-Niedenführ et al (2001) High origin of radial (brachioradial) in 20.3% of sample 192 Embalmed cadavers examined. Variable terminology unified into a homogenous classification following extensive review of literature and meta-analysis of results…”
Section: Discussionmentioning
confidence: 96%
“…All of these reports describe the course of the aberrant vessel as lateral to the usual radial artery. There are no descriptions in the reconstructive and anatomical literature of a superficial and medial branch originating from the radial artery 1.5 cm Weathersby (1956) High origin of radial artery 408 Upper extremities studied revealed departure from normal textbook anatomy in 18.8% of specimens Coleman and Anson (1961) High origin of radial artery 650 Dissected specimens studied Persistent median artery Kadanoff and Balkansky (1966) Duplication of radial artery Case report Small and Millar (1985) Radial artery passing deep to the pronator teres Case report Poteat (1986) Absent radial artery Cadaver dissection single specimen Uglietta and Kadir (1989) High origin of radial artery 100 Upper extremity arteriograms reviewed revealed anomalies of the radial artery in 9% of cases Hedén and Gylbert (1990) Superficial dorsal antebrachial artery Case report Bass (1991) Hypolasia of radial artery Case report e association with VATER syndrome Otsuka and Terauchi (1991) Aberrant dorsal course of radial artery around Lister's tubercle Case report Madaree and McGibbon (1993) Absence of perforators from the radial artery to skin Case report Funk et al (1995) Distal origin of radial artery deep to pronator teres Review of experience with 52 forearm flaps Superficial dorsal antebrachial artery High origin of radial artery Lee et al (1995) Hypoplasia of radial artery Case report e association with KlippeleFeil syndrome Mordick (1995) Aberrant midaxial vessel arising directly from axillary artery Case report Icten et al (1996) High origin of radial artery Case report Sasaki et al (2000) Superficial dorsal antebrachial artery Case report Porter and Mellow (2001) Absent radial artery Case report Rodríguez-Niedenführ et al (2001) High origin of radial (brachioradial) in 20.3% of sample 192 Embalmed cadavers examined. Variable terminology unified into a homogenous classification following extensive review of literature and meta-analysis of results…”
Section: Discussionmentioning
confidence: 96%
“…It is reported that the incidence of variations ranges from 4.4 % to 8.3 % in various samples (Ozcan et al, 2006). Further they have included nonhomogeneous sample or incomplete extremities and have failed to describe the related morphological feature of each of the separate patterns, throughout their whole length in the arm and forearm (Içten et al, 1996). Dimension of the brachial artery and flow-mediated dilatation (FMD) are associated with severity of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…13 There are many such reports on high origin of the radial artery. 14,15 In the present case, the radial artery crossed superficially to the median nerve and then descended laterally to it. While descending in the arm, the radial artery did not give origin to any branches.…”
Section: 11mentioning
confidence: 46%